1969
DOI: 10.1136/bmj.1.5640.357
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Preseasonal and Coseasonal Allpyral with Depo-Medrone in Summer Hay-fever

Abstract: The 12 cases with asbestos body counts of over 10 were all males, and a definite history of industrial asbestos exposure was obtained in 10 cases. The exceptions were an electrician (count 95) and a painter and decorator (count 98). On inquiry by the pathology department it was found that asbestos exposure was a distinct possibility in these cases also.We are indebted to Dr. A. A. M. Gibson for making the results of his asbestos body count survey freely available to us.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

1970
1970
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 8 publications
1
10
1
Order By: Relevance
“…Clinically our patients fared worse than the larger group studied in the previous trial (Ganderton et al, 1969), where 70'%'0 of patients treated with methylprednisolone acetate were improved, and only 2% reported that they had developed asthma for the first time. Three of our six hay-fever patients were improved, but three developed asthma for the first time during the summer.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Clinically our patients fared worse than the larger group studied in the previous trial (Ganderton et al, 1969), where 70'%'0 of patients treated with methylprednisolone acetate were improved, and only 2% reported that they had developed asthma for the first time. Three of our six hay-fever patients were improved, but three developed asthma for the first time during the summer.…”
Section: Discussioncontrasting
confidence: 60%
“…It seemed desirable, therefore, to assess hypothalamic-pituitary-adrenal function in a group of patients receiving methylprednisolone acetate in the dosage used for a recent trial of hay-fever treatment (Ganderton, Brostoff, and Frankland, 1969), when two 80-mg. injections of methylprednisolone acetate were given at an interval of two weeks. The effect on the resting plasma cortisol level, on the response of the adrenal gland to synthetic adrenocorticotrophic hormone (Synacthen), and on the plasma cortisol response to the stress of insulin-induced hypoglycaemia was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Bagratuni (1960) observed that 70% improved on promethazine hydrochloride, 92% on phenindamine tartrate, 55% with prednisolone spray, and 50% with hydrocortisone snuff. Ganderton, Brostoff and Frankland (1969) found 70% improved on depot methyl-prednisolone and 78% on alum-precipitated grass pollen vaccine; and Mygind (1973) found 86% preferred intranasal beclomethasone dipropionate to placebo in a cross-over study similar to our own. The disease itself, although of considerable nuisance to sufferers, is essentially harmless and thus no treatment should be given that might lead to possibly serious side-effects.…”
Section: Discussionsupporting
confidence: 61%
“…This effect exceeds what has been obtained previously with dexamethasone phosphate intranasally (Norman and Winkenwerder, 1965) and depot steroids (Ganderton et al, 1969). While these two drugs always give varying degrees of adrenal suppression, this is apparently not the case with beclomethasone dipropionate aerosol intranasally.…”
Section: Discussionmentioning
confidence: 51%